2007
DOI: 10.1111/j.1525-1594.2007.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Respiratory Variation as an Early Marker of Cardiac Output Fall in Experimental Hemorrhagic Shock

Abstract: Pulse pressure (DeltaPp) and systolic pressure (DeltaPs) variations have been recommended as predictors of fluid responsiveness in critically ill patients. We hypothesized that changes in DeltaPp and DeltaPs parallel alterations in stroke volume (SV) and cardiac output (CO) during hemorrhage, shock, and resuscitation. In anesthetized and mechanically ventilated mongrel dogs, a graded hemorrhage (20 mL/min) was induced to a target mean arterial pressure (MAP) of 40 mm Hg, which was maintained for additional 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
(49 reference statements)
0
20
1
10
Order By: Relevance
“…Lahner et al (20) demonstrated that SVV may not be a reliable predictor of fluid responsiveness in the setting of major abdominal surgery. PPV is considered to be more reliable than SVV and can be used to recognize volume contraction earlier than other indicators (21,22); however, amplified PPV does not represent the hypovolemic status, such as anesthesia or inflammation-induced vasodilation (10). Therefore, restrictive fluid infusion with vasopressor administration during abdominal surgery has been advocated to prevent fluid retention after the anesthetic effects have subsided.…”
Section: Discussionmentioning
confidence: 99%
“…Lahner et al (20) demonstrated that SVV may not be a reliable predictor of fluid responsiveness in the setting of major abdominal surgery. PPV is considered to be more reliable than SVV and can be used to recognize volume contraction earlier than other indicators (21,22); however, amplified PPV does not represent the hypovolemic status, such as anesthesia or inflammation-induced vasodilation (10). Therefore, restrictive fluid infusion with vasopressor administration during abdominal surgery has been advocated to prevent fluid retention after the anesthetic effects have subsided.…”
Section: Discussionmentioning
confidence: 99%
“…Glauco Westphal et al. (17) of the University of São Paulo (São Paulo, Brazil) evaluated if changes in pulse pressure (DeltaPp) and systolic pressure (DeltaPs) parallel alterations in stroke volume (SV) and CO during hemorrhage, shock, and resuscitation. In anesthetized and mechanically ventilated mongrel dogs, a graded hemorrhage (20 mL/min) was induced to a target mean arterial pressure (MAP) of 40 mm Hg, maintained for an additional 30 min.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%
“…The former method is also more reliable than other dynamic parameters, such as systolic pressure respiratory variation (SPV) or stroke volume respiratory variation (SVV), and it can recognize volume contraction earlier than the others 9,10,13. Hence, PPV has become largely recommended to guide volume expansion in patients with hemodynamic instability 912…”
Section: Introductionmentioning
confidence: 99%
“…Patients with low PPV are insensitive to cyclic changes in preload induced by mechanical ventilation, and they operate on the flat portion of the Frank-Starling curve (non-responders). On the other hand, when PPV is high, patients are operating on the steep portion of the Frank-Starling curve and can respond with an increase in SV after fluid infusion (responders) 9,13,15,16…”
Section: Introductionmentioning
confidence: 99%